2021
DOI: 10.1371/journal.pone.0252827
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effects of non-pharmaceutical interventions on the number of new infections with COVID-19 during the first epidemic wave

Abstract: The novel coronavirus (SARS-CoV-2) has rapidly developed into a global epidemic. To control its spread, countries have implemented non-pharmaceutical interventions (NPIs), such as school closures, bans of small gatherings, or even stay-at-home orders. Here we study the effectiveness of seven NPIs in reducing the number of new infections, which was inferred from the reported cases of COVID-19 using a semi-mechanistic Bayesian hierarchical model. Based on data from the first epidemic wave of n = 20 countries (i.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 30 publications
6
61
1
1
Order By: Relevance
“…Because the numbers of cases are nonnegative integers (Supplementary Fig. 2 ), some studies rely on negative binomial regression 21 , 22 , 41 . Therefore, we also applied negative binomial regression to our matched data 52 , using the log of the population size as an offset variable so that various sized municipalities are comparable.…”
Section: Resultsmentioning
confidence: 99%
“…Because the numbers of cases are nonnegative integers (Supplementary Fig. 2 ), some studies rely on negative binomial regression 21 , 22 , 41 . Therefore, we also applied negative binomial regression to our matched data 52 , using the log of the population size as an offset variable so that various sized municipalities are comparable.…”
Section: Resultsmentioning
confidence: 99%
“…Recall that our model requires external knowledge of the delay between infection and case confirmation as well as the delay between infection and death reporting. Many previous studies use estimates for delay distribution based on the data from the first wave 2 , 65 . However, these delay distributions may be different in the second wave due to sustained investment in testing capabilities and healthcare.…”
Section: Methodsmentioning
confidence: 99%
“…Based on data from the first wave of COVID-19, a number of modelling studies provide inconclusive guidance to policy makers. While two publications, one from several countries and one from Switzerland [ 9 , 10 ], concluded that school closures contributed markedly to the reduction of SARS-CoV-2 transmission and individual mobility, respectively, two other studies, one using cross-country data and one from Japan rated school closures among the least effective measures to reduce COVID-19 incidence rates [ 11 , 12 ]. Accordingly, a recent review on SARS-CoV-2 setting-specific transmission rates concluded that there is ‘limited data to explore transmission patterns in […] schools […], highlighting the need for further research in such settings’ [ 13 ].…”
Section: Introductionmentioning
confidence: 99%